Peran dokter puskesmas dalam menerapkan prinsip kedokteran keluarga untuk mencegah difteri di Kota Banda Aceh - Zahratul Aini; Eti Poncorini Pamungkasari; Ari Probandari (Faculty of Medicine, Universitas Islam Indonesia, 2019)
Background: They are expected to be able to apply principles of family-based health treatments by prioritizing preventive, coordinative, and collaborative services. Based on the principles, identifying and managing diphtheria cases at some of health centres should be evaluated because there have been an increase of diphtheria cases, especially in Banda Aceh city.Objective: This study aimed to evaluate roles of doctors in the health centres to prevent the diphtheria. Furthermore, this research also aimed to determine obstacles of the diphtheria treatments encountered by the doctors.Methods: This study was a multiple case study. Its data were collected by in-depth interviews with doctors at five health centres in Banda Aceh. Data from the interviews were verified by using source and technical triangulation methods at the health offices and governmental hospitals in Banda Aceh.Result: Doctors’ efforts at the health centres in Banda Aceh to apply principles of family medicine for the immunization experienced some obstacles. For example, they had less understanding about developing problems in their societies, namely issues of illegitimate (haram) vaccines and KIPI (post-immunization follow-up events). They also did not make active efforts to identify diphtheria cases by making coordination with their colleagues in other health service units.Conclusion: The doctors at the health centres of Banda Aceh had not fully implemented the principles of family medicine.